Pengembangan Kawasan Wisata Edukasi Mangrove pada Era New Normal di Desa Banaran, Galur, Kulon Progo - Paramita, Brigitta Laksmi (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
Banaran Village, Galur, Kulon Progo, Yogyakarta has a Trisik beach as one of the village’s potentials to be developed as tourist attraction. nonetheless the beach are prone to abration. One of the ways to prevent abration is to plant mangrove forest. With the mangrove forest, the villagers could develop it into educational tourism. The development of this educational tourism has to be supported by human resource in Banaran Village. Based on statistic, the human resource Banaran village are sufficient to create this opportunity. This educational tourism also has to be balanced by the implementation of new normal dictated by the government policy.